BAHASA PERSUASIF KAUM MILENIAL PADA PILPRES 2019 - NFN Indrawati (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2018)
This study describes millenials persuasive language in presidential election 2019. It is estimated that a half of the voters in presidential election 2019 are millenials. They are rasional group that have technology literate. That is why each candidates in presidential election 2019 is trying to hold this group. The language of millenials is quite different compare to the common group. Millenials are more creative by using symbol or sentence to persuade public opinion or someone else behaviour. The using of language symbol, spoken or written, sign, drawings signal, is hoped to attract peoiple’s attention and persuade them toward their massage. The aim of this study is to find out the form and meaning of millenials persuasive language in presidential election 2019. This study uses descriptive qualitative method. The data are in the form of document as the result of note taking from social media twitter. The result shows that language persuasive used by millenials in presidential election 2019 contains inviting, meaning explisitly or implisitly. Persuasive language used by millenials in presidential election is in the form of symbol, sentence, and paragraph.